(untitled) (diségno, 2023)
The present study investigates the concept of ‘viewpoints’ in the project of late 19th century theatrical architecture by assessing how the meaning of visual perception of the theatrical scene and the space of the auditorium, hence spectator involvement in the scenic narrative and in social contexts, is changing in the same architectural space. The project choices implemented for the realization of the spaces destined for the booths and stage of the Massimo Bellini theatre in Catania were analysed through the comparison of archival documents of the project, data obtained from digital laser scanning survey, and the analysis of the geometric guides and spectator visibility in comparison with the Italian-style theatre type. The research uses three-dimensional digital models to document the horseshoe planimetric layout of the real space of the booths and its separation from the fictitious stage events through the proscenium, which takes the Renaissance scaenae frons structure delimited by the stage arch to frame the visual region. The survey and analysis clarify the design choices implemented by the architects at a time when the spectator was a central figure and when the theatre represented a dual spectacle involving both the stage space and the space occupied by the spectators.